PERLINDUNGAN HUKUM KEDUDUKAN ANAK PEREMPUAN DALAM HUKUM WARIS ADAT SENTANI DI KABUPATEN JAYAPURA - Kaigere, Sarah Rode Marthina; Tofik Yanuar Chandra; Amelia Nur Widyanti (Bajang Institute, 2025)
According to Sentani customary inheritance law, only male descendants are entitled to inherit the estate of their deceased father. In cases where the father held the position of a traditional leader (Ondoafi or Ondoaho), the right of succession is reserved exclusively for the eldest son. This customary practice has prompted women to challenge the prevailing legal-cultural norms, which they perceive as discriminatory in terms of the roles, rights, and authorities granted to men over women. These women seek equal inheritance rights within the framework of a patrilineal kinship system. This study employs Philipus M. Hadjon’s Theory of Legal Protection and Soepomo’s Theory of Inheritance Law as its theoretical framework. This study employs a normative juridical approach, supported by empirical data, to analyze the position of women in the distribution of inheritance under Sentani customary law, as well as the legal protection afforded to women within the Sentani customary inheritance law system. The data were analyzed using a qualitative juridical analysis method. The research findings indicate that the inheritance system within the Sentani indigenous community adheres to a patrilineal structure, whereby only male descendants are entitled to inherit from their father. In cases where the father serves as a traditional leader (Ondoafi), only the eldest son is designated to succeed his position. Conversely, daughters are not regarded as heirs, but may receive specific possessions—such as kitchen utensils or 'relaar'—during the father's lifetime, particularly if they originate from an Ondofolo family. However, in line with societal developments and the direction of national legal policy, there has been a growing impetus to promote equality in inheritance law. This principle is reflected in the Provisional People’s Consultative Assembly Decree (Tap MPRS) No. II of 1960, reinforced by the Supreme Court of the Republic of Indonesia Decision No. 179/Sip/1961 as a binding jurisprudence, and further affirmed by Law No. 1 of 1974 concerning Marriage, which establishes equal rights and status for men and women within the family and society.